Composition and biological activities of strobilanthes crispus leaves for essential oils extracted by hydrodistillation (HD) and microwave-assisted hydrodistillation (MAHD) methods - Lee, Yong Yong (2016)
Microwave-assisted hydrodistillation (MAHD), an advanced hydrodistillation (HD) method, in which a microwave oven is used to extract essential oil from medicinal plants. MAHD and HD methods have been compared and evaluated for their performance in the isolation of essentials oil from Strobilanthes Crispus leaves. The effect of microwave power, extraction time and water to raw material ratio were investigated to evaluate the best extraction conditions for obtaining maximum oil yield. As a result, the best condition that has been investigated for maximum essential oil production, 0.2016% (w/w) were 450W microwave power for 90 minutes at water to raw material ratio of 10:1. While, HD used 6 hours and water to raw material ratio of 10:1 to achieve the highest yield, 0.1886% (w/w). The composition of the extracted essential oils at different extraction time and microwave power was investigated by GC-MS to evaluate the quality of essential oil. Results shows that the constituent of essential oil from MAHD were different with essential oil from HD. The major constituent of S. Crispus oil from MAHD was Phthalic acid, bis(7-methyloctyl) ester and 1,2-Benzenedicarboxylic acid,mono(2-ethylhexyl)ester. However, the major compound of S. Crispus oil from HD were 1,2-Benzenedicarboxylic acid, decyl hexyl ester and 1,2-Benzenedicarboxylic acid,mono(2-ethylhexyl)ester. This indicates that the use of microwave irradiation influence the composition of essential oils. The maximum oil yield from S. Crispus were obtained at shorter extraction time period with significant influence on their chemical constituents. Therefore, for S. Crispus oil, the method of extraction depends on the uses of the oil. By reviewing the chemical constituents with other studies, Phthalic acid, bis(7-methyloctyl) ester has antimicrobial and antifouling activities whereas 1,2-Benzenedicarboxylic acid,mono(2-ethylhexyl)ester has anticancer activity. This may prove that MAHD can be used to extract large volume and high quality essential oil by using shorter time and saving energy.